2007
DOI: 10.1016/j.ceca.2006.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle-dependent regulation of store-operated ICRAC and Mg2+-nucleotide-regulated MagNuM (TRPM7) currents

Abstract: Calcium signaling is a central mechanism for numerous cellular functions and particularly relevant for immune cell proliferation. However, the role of calcium influx in mitotic cell cycle progression is largely unknown. We here report that proliferating rat mast cells RBL-2H3 tightly control their major store-operated calcium influx pathway, I CRAC , during cell cycle progression. While I CRAC is maintained at control levels during the first gap phase (G1), the current is significantly upregulated in preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 58 publications
4
54
0
Order By: Relevance
“…SOCE is inhibited as the oocyte commits to meiosis (12), and MPF activation is sufficient for SOCE inactivation (12). As is the case in Xenopus eggs, SOCE inactivates during mitosis of mammalian cells (13,18). Here we show that SOCE inactivation during meiosis is the result of Orai1 internalization and to the inability of STIM1 to cluster in response to store depletion.…”
mentioning
confidence: 72%
“…SOCE is inhibited as the oocyte commits to meiosis (12), and MPF activation is sufficient for SOCE inactivation (12). As is the case in Xenopus eggs, SOCE inactivates during mitosis of mammalian cells (13,18). Here we show that SOCE inactivation during meiosis is the result of Orai1 internalization and to the inability of STIM1 to cluster in response to store depletion.…”
mentioning
confidence: 72%
“…Furthermore, as is the case in Xenopus eggs, SOCE inactivates during mitosis of mammalian cells (Preston et al, 1991;Tani et al, 2007), arguing that MPF activation typically leads to SOCE inactivation, since mitosis also requires MPF/cdk1. Therefore, mammalian eggs are the exception in terms of maintaining SOCE functional during the division phase of the cell cycle.…”
Section: Store-operated Ca 2r Entry (Soce)mentioning
confidence: 99%
“…We recently observed that, unlike interphase cells, the depletion of intracellular calcium stores with ATP was not followed by SOCE in mitotic cells which indicates the inhibition of this vital [Ca 2+ ]i -regulating mechanism. A few reports have implied either a down-regulation or a complete absence of SOCE in mitotic cells presumably due to uncoupling between cell surface channels and the ER (Volpi and Berlin, 1988;Preston et al, 1991;Tani et al, 2007). However, no attempts have been made to substantiate these findings and possibly shed some light on the cellular mechanisms involved.…”
Section: Laser Scanning Confocal Microscopy To Monitor [Ca 2+ ]I D Y mentioning
confidence: 88%